2014
DOI: 10.1063/1.4878622
|View full text |Cite
|
Sign up to set email alerts
|

Downstream plasma transport and metal ionization in a high-powered pulsed-plasma magnetron

Abstract: Design and characterization of 2.45 GHz electron cyclotron resonance plasma source with magnetron magnetic field configuration for high flux of hyperthermal neutral beam Rev. Sci. Instrum. 81, 083301 (2010); 10.1063/1.3477998Sheath and potential characteristics in rf magnetron sputtering plasma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Several authors studied the temporal fluctuations in the floating potential and some associated it with the moving ionization zones. 8,[33][34][35][36][37] Such measurements are relatively simple but offer a little insight into the properties of plasma since the motion of charged particles is affected by the gradient of the plasma potential and not by the gradient of the floating potential.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors studied the temporal fluctuations in the floating potential and some associated it with the moving ionization zones. 8,[33][34][35][36][37] Such measurements are relatively simple but offer a little insight into the properties of plasma since the motion of charged particles is affected by the gradient of the plasma potential and not by the gradient of the floating potential.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in HiPIMS, the plasma expansion is associated with a high plasma density peak moving from the target towards the substrate with the magnetic field strength controlling the downstream plasma distribution. 16 The "Spiral" magnet pack described in Yu et al 17 showed a flattened downstream plasma density distribution in HiPIMS. Also, TLP measurements on "Spiral" magnetic field pattern demonstrated more uniform downstream plasma density compared to the other magnetic field patterns tested in that work.…”
Section: / Trimentioning
confidence: 98%
“…ACCEPTED MANUSCRIPT 9 to the conventional pack discharge, as described by Thornton, J. A et al [17].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3 magnetic field profile on the magnetron target surface [8][9][10], plasma impedance [11], plasma instabilities [12] and power supply pulsing parameters [13,14].…”
Section: Accepted Manuscriptmentioning
confidence: 99%